Подождите немного. Документ загружается.
90
0
l
1
l
2
m
1
m
2
α
q
i
(t)
˜q
i
(t) q
i
(t)
˜q
i
(t) = q
i
(t) + δq
i
(t).
˙
˜q
i
(t) = ˙q
i
(t) +
d
dt
δq
i
(t).
δ ˙q
i
=
˙
˜q
i
− ˙q
i
=
d
dt
δq
i
(t).
t
1
t
2
δq
i
(t
1
) = δq
i
(t
2
) = 0.
˜
S
δq
i
δ ˙q
i
˜
S =
Z
t
2
t
1
L(
˙
˜q
i
, ˜q
i
, t) dt =
Z
t
2
t
1
L( ˙q
i
, q
i
, t) dt +
Z
t
2
t
1
(
X
i
∂L
∂ ˙q
i
δ ˙q
i
+
X
i
∂L
∂q
i
δq
i
) dt.
Z
t
2
t
1
∂L
∂ ˙q
i
δ
˙
q
i
dt =
Z
t
2
t
1
∂L
∂ ˙q
i
d
dt
(δq
i
) dt =
∂L
∂ ˙q
i
δq
i
¯
¯
¯
¯
¯
¯
t2
t1
−
Z
t
2
t
1
d
dt
(
∂L
∂ ˙q
i
)δq
i
dt.
δq
i
= 0
δS =
˜
S − S =
Z
t
2
t
1
X
i
(
∂L
∂q
i
−
d
dt
∂L
∂ ˙q
i
)δq
i
dt = 0.
δq
i
i
d
dt
∂L
∂ ˙q
i
−
∂L
∂q
i
= 0.
q
i
(t)
L L
0
F (q
i
, t)
L
0
= L +
d
dt
F (q
i
, t).
S
0
− S =
Z
t
2
t
1
dF
dt
dt = F (q
i
(t
2
), t
2
) − F (q
i
(t
1
), t
1
).
t
1
t
2
S S
0
q
i
(t)
L
0
L
d
dt
∂L
∂ ˙q
i
−
∂L
∂q
i
= f
i
, f
i
=
X
a
~
f
a
∂~r
a
∂q
i
.
f
i
= −
∂Φ
∂ ˙q
i
, Φ =
1
2
X
i,j
α
ij
˙q
i
˙q
j
.
α
ij
d
dt
∂L
∂ ˙q
i
−
∂L
∂q
i
= −
∂Φ
∂ ˙q
i
.
e
L = T − eϕ −
e
c
~
A~v,
ϕ
~
A
c
m
U(~r)
L =
1
2
mv
2
− U(~r) =
1
2
m( ˙x
2
+ ˙y
2
+ ˙z
2
) − U(x, y, z).
d
dt
∂L
∂ ˙x
−
∂L
∂x
= 0,
d
dt
∂L
∂ ˙y
−
∂L
∂y
= 0,
d
dt
∂L
∂ ˙z
−
∂L
∂z
= 0.
x,
˙
x, y,
˙
y z,
˙
z
x
˙x
∂L
∂x
= −
∂U
∂x
,
∂L
∂ ˙x
= m ˙x.
m¨x = −
∂U
∂x
, m¨y = −
∂U
∂y
, m¨z = −
∂U
∂z
.
r, ϕ, z
L =
1
2
mv
2
− U(~r) =
1
2
m( ˙r
2
+ r
2
˙ϕ
2
+ ˙z
2
) − U(r, ϕ, z).
z
r, ϕ
d
dt
∂L
∂
˙
r
−
∂L
∂r
= 0,
d
dt
∂L
∂
˙
ϕ
−
∂L
∂ϕ
= 0.
∂L
∂r
= mr
˙
ϕ
2
−
∂U
∂r
,
∂L
∂ ˙r
= m
˙
r,
∂L
∂ϕ
= −
∂U
∂ϕ
,
∂L
∂
˙
ϕ
= mr
2
˙ϕ.
r ϕ
m(¨r − r ˙ϕ
2
) = −
∂U
∂r
,